Taux d'endemicité et tendances phytogeographiques de la végétation psammophile des plages et des dunes de sable côtier dans le sud-ouest de l'Europe (Portugal continental) - Martins, Mónica C. (2015)
In southwest Europe (mainland Portugal), the psammophilic ecosystems of coastal beaches and sand dunes are distributed by the Eurosiberian (EUR) and Mediterranean (MED) biogeographic regions. In addition to climatic and other environmental factors, distinct plant communities are mainly influenced by the instability of the coastal sands and the proximity to the sea. Psammophilic gradients determine the plant communities that occur from the first sectors of the beach until the more interior dunes, being expressed by specific floristic associations and different rates of cover, namely by endemic taxa. The analysis of 601 phytosociological relevés, conducted between 1972 and 2010, from north (Minho) to the south (Alentejo and Algarve), allowed to study the dominant communities which occur along the ecological gradient sea-interior, with the aim of better understand general spatial geomorphologic and phytogeographic trends of distribution. As for the sea-interior gradient, no endemic flora appears in the first vegetation strip (annual communities of drift lines). Yet, some endemic species appear in the embryonic shifting dunes of the back beach, with endemic species’ coverage of 1.07% (EUR) and 1.7% (MED). In the mobile dunes (white dunes) covers by endemic flora are more significant: 6.95% (EUR) against 4.14% (MED). Semi-stable dune (gray dune), is composed by three associations (EUR, MED and another of Transition (ART) which occurs between the former two), who have the highest covers for endemics: 38,89% (EUR) 43,37% (TRA) and 55,85% (MED). Do not considering specific human induced situations of degradation and erosion, a general trend of gradual coverage growth by endemic taxa, was signed from north to south, despite median overall covers (total species) are higher in the north. The endemic taxa have been separated into endemic Portuguese (EP), Iberian (EI) and European (EU) and its representativeness endorsed. The interest in the use of phytosociology in this kind of study is discussed